PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS: STUDI SLR TERHADAP KENDALA GURU DI NEGARA BERKEMBANG - Supriyanto; Widati, Danik; Fuad Abdul Baqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education has become a global priority to ensure equal access to quality education for children with special needs. However, its implementation in developing countries remains challenging, particularly for teachers who play a central role in inclusive classrooms. This study aims to systematically examine the challenges faced by teachers in implementing inclusive education for children with special needs in developing countries through a Systematic Literature Review (SLR). The review analyzed peer-reviewed national and international journal articles published between 2021 and 2025 and retrieved from academic databases relevant to inclusive education. The findings reveal that teachers encounter multidimensional challenges, including limited pedagogical competence, psychological burden, inadequate institutional support, policy–practice gaps, and socio-cultural barriers. These challenges are interrelated and reflect broader systemic issues within educational systems in developing countries. This study provides a comprehensive synthesis of recent evidence and offers insights for policymakers, educational institutions, and teacher education programs to strengthen inclusive education through systemic and sustainable approaches. Keywords: inclusive education, children with special needs, teacher challenges, developing countries, systematic literature review